A Review on Indian Financial Management and Women Entrepreneurship - Bibhuti B Pradhan (International Journal of Psychosocial Rehabilitation, 2019)
The driving forces behind economic development have been small and medium-sized businesses worldwide. Women entrepreneurship has proven time consuming in India, but most of these women-driven companies have shown marginal signs of growth. With women entrepreneurs lacking growth, research aimed at considering women entrepreneurs ’ strategies for financial management (FM). The study recognized women entrepreneurs ’ challenges in running their business finances. The paper shows that businessmen must realize that without proper financial management, development and company success are fruitless and must look for sufficient guidance and expertise in managing resources effectively. Researches in relation to the priorities of men and woman-led firms suggest that women owners frequently seek economic and social agendas that could hinder economic performance or development. In his view, discrimination retards growth, partially because it restricts access to important services such as employment, health, property, land and other resources to large parts of the population. Unfairness has created poverty.